Perceived Organizational Support Dan Dynamic Ambidexterity Capabilities Sebagai Upaya Strategi Untuk Meningkatkan Creative Problem Solving ( Study Karyawan Pada Pt Citra Sarung Tangan Indonesia (CSindo)) - Saputro, Luthfi Nugroho; Kurniawan, Ignatius Soni (Universitas Muhammadiyah Metro, 2021)
Having creative human resources is a must for companies today, because companies must always be innovative to face competition. This study aims to determine the perceived organizational support and dynamic ambiance capabilities as a strategic effort to increase the creative problem solving study of employees at PT. Indonesian Glove Image (CSINDO). Primary data were collected using a questionnaire distributed to employees. The results showed that perceived organizational support has an effect on creative problem solving, as well as perceived organizational support and dynamic ambidexterity capabilities have a positive effect on creative problem solving